Deskriptif Literasi Keuangan Peserta Didik SMA Negeri 5 Pontianak - Fitri Andhriani fitriandhriani; Maria Ulfah; Achmadi Achmadi (Peneliti.net, 2023)
The purpose of this study was to analyze the financial literacy of Pontianak 5 Public High School students. The method used in this research is descriptive method with a survey research form. The subjects of this study were students of SMA Negeri 5 Pontianak. The data collection technique used interview sheets and direct observation and the data analysis technique used in this study was descriptive qualitative analysis. Based on the results of the research, it was concluded that the financial literacy of students at SMA Negeri 5 Pontianak has an ideal score on the financial literacy indicator with an average value of 76%. The current value is in the range of 60.1% to 80%, which indicates that the value is in the high category.